Artificial intelligence in the work context. (21st December 2022) - Jarrahi, Mohammad Hossein; Lutz, Christoph; Boyd, Karen; Oesterlund, Carsten; Willis, Matthew
Abstract: Artificial intelligence (AI) reconfigures work and organization, while work and organization shape AI. In this special issue, we explore these mutual transformations and how they play out across industries and occupations. We argue that, to truly appreciate this transformative power, the use of AI should be understood in relation to key dimensions of the work context. In this editorial, we discuss the sociotechnical dynamics of AI implementation, the research landscape of AI in the context of work, and key contextual factors on the macro‐ and micro‐level that help understand the AI‐work nexus. We then provide directions for future research at the intersection of work and AI.